ORGANIZING LECTURE ACTIVITIES EFFECTIVELY IN FOREIGN LANGUAGES - Y. U. Abdurazzokov (Galaxy International Interdisciplinary Research Journal, 2022)
This article deals with the issue how to increase the efficiency of teaching German language. It also describes innovative methods and ways of teaching German during lecture classes. In order to identify the main components, which are necessary for the implementation of this model of teaching students in a foreign language, the possibilities of expanding the powers of professors in the issues of modern teaching methods are highlighted